PELATIHAN ENGLISH SPEAKING BERBASIS ARTIFICIAL INTELLIGENCE UNTUK MENINGKATKAN SELF-CONFIDENCE MAHASISWA - Cahyadi; Dwi Purnomo; Heri Wiranto; Fajar Maula Hidayat; Hafidz Sanjaya (Jurnal Pengabdian Kepada Masyarakat, 2026)
The rapid development of Artificial Intelligence (AI) has significantly influenced various educational practices, including English language learning. Many students still experience difficulties in speaking English due to low self-confidence, fear of making mistakes, and limited opportunities for speaking practice. This community service activity aimed to enhance students’ self-confidence through AI-based English speaking training. The program involved 25 students who participated in interactive speaking practices using AI applications such as ChatGPT and AI voice assistants. The methods employed included training sessions, demonstrations, guided speaking practice, discussions, and evaluations through questionnaires and observations. The results indicated that participants experienced improvements in self-confidence, motivation, and speaking participation after attending the training. Students perceived AI-based learning as a flexible, interactive, and supportive medium for independent speaking practice. Furthermore, the implementation of AI in English language learning created a more comfortable learning environment, reducing speaking anxiety. Therefore, AI-based speaking training was found to be effective in enhancing students’ self-confidence and communication skills in English language learning.